METODE PEMBELAJARAN DISCOVERY LEARNING DENGAN PENDEKATAN SAINTIFIK PADA PEMBELAJARAN MATEMATIKA ZAKAT DAN FARAIDH - Mochamad Nashrullah; Ida Rindaningsih (Edukasi Islami : Jurnal Pendidikan Islam, 2014)
Learning is a process that contains a set of actions of teachers and students on the basis of reciprocal relationships that take place in the situation of education in order to achieve certain goals. The interrelationship between the teacher and the students are the main requirements the process of learning. Interactions in learning not only the relationship between teachers and students, but in the form of educational interaction Basic skills that a teacher should possess the ability to plan and implement the learning process. The process of learning is the provision of teachers in carrying out their duties and responsibilities as educators. Success in educating teachers is one of the determinants of a student for the better, many of the tasks and responsibilities carried jawabyang teachers in an educational process. A process that can be felt by students in learning activities is the duty of teachers to teach. Teaching and learning can be done by using various methods. Therefore, when learning mengajardilakukan will make the students sick and tired.